I Certamen Crono-Teatro (2013). Modalidad de vagón 11. Medea furens - Pygmalión (Pygmalion. Revista de teatro general y comparado, 2025)
I Certamen Crono-Teatro (2013). Modalidad de vagón 11. Medea furens